2014
DOI: 10.2147/dmso.s66156
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiometabolic risk factors and metabolic syndrome in obese Kuwaiti adolescents

Abstract: BackgroundChildhood and adolescent obesity is associated with insulin resistance, abnormal glucose metabolism, hypertension, dyslipidemia, inflammation, liver disease, and compromised vascular function. The purpose of this pilot study was to determine the prevalence of cardiometabolic risk factor abnormalities and metabolic syndrome (MetS) in a sample of obese Kuwaiti adolescents, as prevalence data might be helpful in improving engagement with obesity treatment in future.MethodsEighty obese Kuwaiti adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…While the obese Copyright © JCEI / Journal of Clinical and Experimental Investigations 2016 | www.jceionline.org subjects in this study had higher very low-density lipoprotein (VLDL) and triglycerides (TG), and lower high-density lipoprotein (HDL) levels than the control subjects, no difference was observed in the total cholesterol (TC) and low-density lipoprotein (LDL) values. A strong correlation with insulin resistance of dyslipidemias, especially high TG or low HDL levels, has also been reported in published studies [9].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…While the obese Copyright © JCEI / Journal of Clinical and Experimental Investigations 2016 | www.jceionline.org subjects in this study had higher very low-density lipoprotein (VLDL) and triglycerides (TG), and lower high-density lipoprotein (HDL) levels than the control subjects, no difference was observed in the total cholesterol (TC) and low-density lipoprotein (LDL) values. A strong correlation with insulin resistance of dyslipidemias, especially high TG or low HDL levels, has also been reported in published studies [9].…”
Section: Discussionsupporting
confidence: 63%
“…Insulin resistance is recognized as an important risk factor for DM (9). HOMA-IR is often used to evaluate the level of insulin resistance [6].…”
Section: Discussionmentioning
confidence: 99%
“…After puberty, and possibly through a mechanism involving sexual hormones, adiponectin decreases with age in both genders, more markedly in boys [72,130]. Several studies have reported similar adiponectin levels for both genders, even in OB paediatric populations involving post-pubertal subjects [10,29,61,111,131].…”
Section: Conclusion and Final Remarksmentioning
confidence: 98%
“…A number of epidemiological studies have suggested that childhood obesity is an independent risk factor of chronic diseases later in life 1 2 3 4 . Thus, identifying modifiable risk factors of obesity in childhood is of great public health significance.…”
mentioning
confidence: 99%